1992
DOI: 10.1002/ajmg.1320440622
|View full text |Cite
|
Sign up to set email alerts
|

False‐negative prenatal diagnosis of restrictive dermopathy

Abstract: Restrictive dermopathy is a rare autosomal recessive lethal skin dysplasia. It has been assumed that the characteristic morphologic abnormalities should allow a reliable prenatal diagnosis on fetal skin biopsies at about 20 weeks pregnancy. We report on a false-negative prenatal diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
3

Year Published

1993
1993
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 7 publications
0
11
0
3
Order By: Relevance
“…Because of the high risk of recurrence in subsequent pregnancies, there is a need for prenatal diagnosis. Skin biopsy is not reliable, as Hamel et al [1992] showed. Unfortunately, all specific changes seem to develop after 22 weeks of gestation.…”
Section: Discussionmentioning
confidence: 94%
“…Because of the high risk of recurrence in subsequent pregnancies, there is a need for prenatal diagnosis. Skin biopsy is not reliable, as Hamel et al [1992] showed. Unfortunately, all specific changes seem to develop after 22 weeks of gestation.…”
Section: Discussionmentioning
confidence: 94%
“…Hamel et al performed skin biopsies at 20 weeks on several cases of restrictive dermopathy and could not demonstrate any skin abnormalities. They concluded that these abnormalities develop only later in fetal life 10 .…”
Section: Restrictive Dermopathy: Two-and Three-dimensional Sonographimentioning
confidence: 99%
“…Eindeutige histologische Veränderungen treten erst nach der 20.-22. SSW auf [8,10,17,21], wenn die mesenchymale Entwicklung der Dermis und die Keratinisation der Epidermis sich dem Ende zuneigt [26,27]. Hamel und Mitarbeiter berichten über einen Fall, in dem fetale Hautbiopsien in der 20.…”
Section: Fazit Für Die Praxisunclassified
“…Hamel und Mitarbeiter berichten über einen Fall, in dem fetale Hautbiopsien in der 20. SSW einen falsch-negativen Befund ergaben [8,10]. Erst nach der 21.…”
Section: Fazit Für Die Praxisunclassified
See 1 more Smart Citation